Construction of diagnostic prediction model for Wilson's disease - Wang, Yao; Li, Yulian; Xun, Linting; Song, Zhengji (Frontiers in Surgery, 2023)
Wilson’s disease also known as hepatolenticular degeneration, is a rare human autosomal recessive inherited disorder of copper metabolism. The clinical manifestations are diverse, and the diagnosis and treatment are often delayed. The purpose of this study is to establish a new predictive diagnostic model of Wilson’s disease and evaluate its predictive efficacy by multivariate regression analysis of small trauma, good accuracy, low cost and quantifiable serological indicators, in order to identify Wilson’s disease early, improve the diagnosis rate and clarify the treatment plan.